The Psychological Impact of Colour and Music on Concentration - Singh Aliya; Stopforth Riaan; Rampath Amaan; Hands Clive (MATEC Web of Conferences, 2022)
This paper details the research conducted as vacation work undertaken for Touch Prosthetics during which an electroencephalogram (EEG) headset was used to analyse psychological priming effects on subjects’ concentration levels using visual and audial stimuli. The experimental procedure consists of a visual aspect and an audial aspect during which a participant’s brain activity was measured when exposed to their self-reported favourite colour or music genre, respectively. The findings of both aspects of the experiment may have applications in an industrial environment as a measure to improve employee concentration, and consequently ensure health and safety by minimising hazards due to poor concentration.